Identification of LSM family members as potential chemoresistance predictive and therapeutic biomarkers for gastric cancer - Liu, Qianhui; Lian, Qinghai; Song, Yingqiu; Yang, Shangbin; Jia, Changchang; Fang, Jiafeng (Frontiers in Oncology, 2023)
Background: The Like-Smith (LSM) family plays a critical role in the progression of several cancers. However, the function of LSMs in chemoresistance of gastric cancer (GC) is still elusive. Methods: The Cancer Genome Atlas (TCGA) database, Gene Expression Omnibus (GEO) database and Tumor Immune Estimation Resource Analysis (TIMER) were utilized to analyze the expression, prognostic value and immune infiltration of LSMs in GC patients. Moreover, qPCR and immunohistochemistry (IHC) experiment were conducted with clinical samples. Results: The expression of LSMs was upregulated in GC tissues and most of LSMs were negatively correlated with overall survival of GC patients with 5-fluorouracil (5-FU) treatment. We further revealed that LSM5, 7 and 8 were hub genes of GEO (GSE14210). Besides, the qPCR results demonstrated that a higher level of LSM5 and LSM8 was associated with 5-FU chemoresistance in GC. Moreover, both TIMER and IHC revealed that a lower expression of LSM5 and LSM8 was correlated with high infiltration of T cells, regulatory T cells, B cells, macrophages, and neutrophils. Conclusions: Our study systematically investigated the expression pattern and biological features of LSM family members in GC, and identified LSM5 and LSM8 as potential biomarkers in GC with 5-FU chemotherapy.